Skip to content

Commit

Permalink
Update 1.md
Browse files Browse the repository at this point in the history
  • Loading branch information
mllabovitz authored Jan 6, 2024
1 parent d57a88c commit 5f28ac7
Showing 1 changed file with 55 additions and 1 deletion.
Original file line number Diff line number Diff line change
Expand Up @@ -5,4 +5,58 @@ statement: |
$$X(x) = \begin{cases} 1, &x \le 2\\\\ 2, &otherwise\end{cases}$$
Compute the pmf of $X$
---
Let $Y be a random varable defined with positive probability over the outcome space {1, 2, 3, 4, 5, 6}
Let $Y$ be a random varable defined with positive probability over the outcome space $\{1, 2, 3, 4, 5, 6\}$

Define the probability of $Y$ as follows:

$$
P(Y = y) =
\begin{cases}
\frac{1}{6} & \text{for } y \in \{1,2,3,4,5,6\} \\
0 & \text{otherwise}
\end{cases}
$$

The implication of the defined transformation is

$$
\begin{aligned}
Y = \{1,2\} & \Rightarrow X = 1 \\
Y = \{3,4,5,6\} & \Rightarrow X = 2
\end{aligned}
$$

In bracket notation, let random variable $X: \Omega \rightarrow \mathbb{R}$ be defined as,

$$
X(x) = \begin{cases} 1, &y \le 2\\\\ 2, &y \in \{1,2,3,4,5,6\}\end{cases}
$$

Computing inducted probabilities, we have

$$
P(X = 1) = P(Y = 1 \cup Y = 2) = \text{ (Independence) } P(Y = 1) + P(Y = 2) = \frac{1}{6} + \frac{1}{6} = \frac{1}{3}
$$

By law of complementary probability and the definition of the output space of $X$ we have

$$
P(X=2) = 1 - P(X=2) = \frac{2}{3}
$$

or

$$
P(X = 2) = P(Y = 3 \cup Y = 4 \cup Y = 5 \cup Y = 6) = \text{ (Independence) } P(Y = 3) + P(Y = 4) + P(Y = 5) P(Y = 6) =
\frac{1}{6} + \frac{1}{6} + \frac{1}{6} + \frac{1}{6}= \frac{2}{3}
$$

The PMF of X is

$$
P(X=x) = \begin{cases} \frac{1}{3}, &x = 1\\\\ \frac{2}{3}, &x =2 \\\\ 0, &otherwise\end{cases}
$$




0 comments on commit 5f28ac7

Please sign in to comment.